THE PROBLEM OF LEXICAL WORDS COLLOCATION UNDER THE PROCESS OF TRANSLATION - Rimma N. Dmitrieva (Вестник Северо-Кавказского федерального университета)
The article is devoted to the problem of lexical compatibility of words in the course of translation. Sentence structure in the process of speaking is involved in the difficult system of traditions and rules, which in fluencies the choice of words and their mutual word order. If the reader or listener finds the sentence difficult to perceive it is caused by breaking the grammar rules of lexical compatibility of words. Lexical compatibility laws determine the words coincidence due to their lexical meaning, rather than their grammatical characteristics.